Formation of the profit management system of the enterprise: an innovative approach - Ostapenko, V.; Tokhtamysh, T. (НДІ ПЗІР НАПрН України, 2023)
The article proposes an innovative approach to the formation of the company’s profit management system, which will help achieve effective results and ensure competitiveness. It has been proven that profit management is one of the key aspects of the successful operation of any enterprise. Ensuring a stable and growing level of profit becomes a challenge in today’s business environment characterized by constant changes and competitive pressure. The article analyzes modern trends in profit management, including the role of strategic planning, cost and profitability analysis, risk management, and the implementation of innovative approaches. The main components of an innovative approach to profit management are considered, including the introduction of new technologies and processes, the creation of new products and services, the optimization of costs and the provision of effective control. Special attention is paid to the consideration of tools and methods that can be used to form a profit management system at the enterprise. It is proposed to use a balance sheet approach that takes into account not only financial indicators, but also intangible assets, customer base and other factors. In addition, profit forecasting models are considered, which allow accurate estimations and planning of future results. Specific examples of successful implementation of an innovative approach to profit management at various enterprises are considered, as well as case studies of companies that were able to achieve significant improvements in their financial indicators due to the implementation of new strategies and profit management tools. In order for the company’s management to be ready for the implementation of new strategies and tools, it is recommended to use modern information technologies for data collection and analysis. The article proposes an innovative approach to the formation of the company’s profit management system, which will ensure its stability and competitiveness in the market. The implementation of new strategies, tools and technologies will allow to achieve effective profit management, as well as to ensure the growth and development of the enterprise in the modern business environment. У статті пропонується інноваційний підхід до формування системи управління прибутком підприємства, який вплине на досягнення ефективних результатів та забезпечить конкурентоспроможність. Доведено, що управління прибутком є одним із ключових аспектів успішної діяльності будь-якого підприємства. Забезпечення стабільного та зростаючого рівня прибутку стає викликом у сучасному бізнессередовищі, що характеризується постійними змінами та конкурентним тиском. У статті проведено аналіз сучасних тенденцій управління прибутком, включаючи роль стратегічного планування, аналізу витрат та прибутковості, управління ризиками та впровадження інноваційних підходів. Розглянуто основні складові інноваційного підходу до управління прибутком, включаючи застосування нових технологій та процесів, створення нових продуктів та послуг, оптимізацію витрат та забезпечення ефективного контролю. Особлива увага приділяється розгляду інструментів та методик, які можуть бути використані для формування системи управління прибутком на підприємстві. Запропоновано використовувати балансовий підхід, який враховує не тільки фінансові показники, але й нематеріальні активи, клієнтську базу та інші фактори. Крім того, розглядаються моделі прогнозування прибутку, які дозволяють зробити точні оцінки та планувати майбутні результати. Розглянуто приклади успішного впровадження інноваційного підходу до управління прибутком на різних підприємствах, а також досліджено кейси компаній, які змогли досягти значних покращень у своїх фінансових показниках завдяки впровадженню нових стратегій та інструментів управління прибутком. Для того, щоб керівництво підприємства було готове до впровадження нових стратегій та інструментів, рекомендовано використовувати сучасні інформаційні технології для збору та аналізу даних. У статті запропоновано інноваційний підхід до формування системи управління прибутком підприємства, який забезпечить його стабільність та конкурентоспроможність на ринку. Впровадження нових стратегій, інструментів та технологій дозволить досягти ефективного управління прибутком, а також забезпечити зростання та розвиток підприємства в сучасному бізнес-середовищі.
Keywords: costs; efficiency; enterprise; profit management; управління прибутком